REVITALIZING THE APPLICATION OF PANCASILA VALUES THROUGH MODELING THE LONTO LEOK CULTURE OF THE MANGGARAI COMMUNITY, EASTERN INDONESIA - Effendi, Yulius R (UI Scholars Hub, 2025)
This study explores the potential for integrating Lonto Leok culture as a character education model based on Pancasila values in schools. This research employs a qualitative approach utilizing a case study methodology. Data were collected through interviews, observations, and document analysis in Manggarai communities and schools that have integrated the Lonto Leok cultural tradition into their learning processes. The data analysis confidently employed a triangulation approach to solidify the validity of the research outcomes, ensuring their credibility, dependability, transferability, and confirmability. The research results indicate that the values espoused in Lonto Leok culture, including religiosity, deliberation, unity, peace, and justice, are highly consistent with the principles of Pancasila. The integration of these values in school learning can enhance students' comprehension and appreciation of Pancasila while also reinforcing their character through pertinent and contextual approaches. This research proposes the utilization of Lonto Leok culture as a means of fortifying Pancasila-based character education in the context of the challenges posed by globalization. This report recommends that the Indonesian Ministry of Education adopt a new curriculum to strengthen Pancasila education in primary and secondary schools.